Kemampuan Membaca Memahami Teks Deskripsi Bahasa Jerman - Ramliah, Ramliah; Mannahali, Misnah; Rijal, Syamsu (Academic : Journal of Social and Educational Studies, 2025)
Abstract. This research is a descriptive qualitative study. The aim of the research is to determine the ability of students in class XI.9 at SMA Negeri 3 Makassar to comprehend descriptive texts in German. The population of this study consists of five eleventh-grade classes, and the selected sample was class XI.9, which includes 30 students chosen through random sampling. The data were obtained through two types of reading comprehension tests: multiple-choice (Mehrfachauswahl) and true-false (Richtig-Falsch) tests. The data were analyzed using percentage techniques. The results showed that the students’ ability to comprehend descriptive texts in German was in the “good” category, with an average score of 82%Keywords: Ability, Reading Comprehension, Descriptive texts